2003
DOI: 10.1017/s0021859603003629
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and growth response to irrigation and sowing date of Kabuli chickpea (Cicer arietinum L.) in a cool-temperate subhumid climate

Abstract: The photothermal response of three Kabuli chickpea (Cicer arietinum L.) cultivars, at different growth stages, to eight irrigation treatments in 1998/99 and four irrigation treatments in 1999/2000 was studied on a Wakanui silt loam soil in Canterbury, New Zealand (43°38S, 172°30E). The rate of development from emergence to flowering (e-f) and sowing to harvest maturity were strongly and positively associated (R2=0·87, P<0·001) with mean temperature during those periods. All phenological stages considered (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…1). Similar results were reported by Anwar et al (2003b) who suggested that the fl owering period, like the vegetative phase, has a key role in determining overall growthperiod duration.…”
Section: Phenological Developmentsupporting
confidence: 88%
See 1 more Smart Citation
“…1). Similar results were reported by Anwar et al (2003b) who suggested that the fl owering period, like the vegetative phase, has a key role in determining overall growthperiod duration.…”
Section: Phenological Developmentsupporting
confidence: 88%
“…Aboveground plant biomass was measured every 15 d from seedling stage (two true leaves unfolded) to harvest. Phenological development was recorded twice weekly for both cultivars, using the scale proposed by Anwar et al (2003b): emergence (the time when 50% of plant density goal had emerged in any plot); flowering (50% of plants had one open flower at any node on the main stem in any plot); podset (50% of plants had at least one emerged green pod in any plot); physiological maturity (50% of the plants had at least one mature (brown) pod in any plot); and harvest maturity (when plants were considered harvest ready). Phenological development measurements were averaged for the two cultivars because they were very similar.…”
Section: Methodsmentioning
confidence: 99%
“…In faba bean, only one type of inoculum was used (ISL-19 isolate), as well as an uninoculated control. The number of pots of inoculated plants was duplicated in order to sample the plant at full flowering and seed maturity, according to the phenological scales proposed by Anwar et al (2003) for chickpea and Knott (1990) for faba bean.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental design, site and husbandry methods are fully described in the companion paper (Anwar et al 2003). Briefly, two experiments were carried out at Lincoln University, New Zealand.…”
Section: Methodsmentioning
confidence: 99%
“…Early sowing had a dominant positive effect on total intercepted PAR, as the irrigation by sowing date and sowing date by cultivar interactions indicated that the response to irrigation depended on the sowing date. The amount of incident solar radiation was different at all the sowing dates (Anwar et al 2003). This, coupled with variation in canopy characteristics (GAI and GAD), perhaps resulted in differences in total intercepted PAR between irrigation treatments within a sowing date.…”
Section: Dry Matter Productionmentioning
confidence: 99%